EXPLORING THE IMPACT OF CORPORATE GOVERNANCE AND AUDIT COMMITTEE CHARACTERISTICS ON EARNINGS MANAGEMENT - Yin, Shang (2019)
The market always needs to use the accurate financial information provided by enterprises for proper operation and development. Companies should prepare financial statements to reflect the performance of the past year. Taking this information into account, investors can decide whether or not to invest. Some people think that companies involved in earnings management cannot show the real financial situation to investors, which covers the real information that stakeholders should know and affects the authenticity of market information (Loomis, 1999). Thus, detecting and preventing opportunistic earnings management has become an indispensable part in process of oversight, and board of directors and audit committees should take the responsibility to oversight the reported earnings and protect investors from information asymmetry, then improve the confidence of investors to companies and market. Therefore, building an effective corporate governance system is of great importance for companies as they should take the responsibility to provide information to investors as accurate as possible to protect their informative rights. For British companies, the boards and their appointed committees are responsible for major regulatory issues. The purpose of this study is to study the effectiveness of the supervisory functions of the board of directors and the audit committee in improving the quality of reported earnings. After clarifying its impact on earnings management, the results can be used to provide some suggestions for enterprises to adjust the existing corporate governance structure, audit committee structure and business model, so as to help enterprises improve the quality of earnings disclosure. This paper focuses on the relationship between earnings management and the independence, the size, financial expertise, duality of the board of directors, the size, financial expertise, the meeting frequency, and the independence of the audit committee. Panel data regression analysis is the main method, which is a method that utilizes statistics to bring about relationship between independent variables and dependent variable. Panel data analysis is considered to be superior than cross-sectional and time series analysis. The study found that in the two sets of independent variables, except for the board size and the duality of CEO, all the rest variables were significantly negatively correlated with earnings management. The results of this study show that among the two groups of independent variables, narrowing the board size, reducing the existence of the duality of CEO, strengthening board financial skills, increasing the board independence, expanding the audit committee size, increasing the audit committee independence, enriching the number of audit committee meetings, and promoting the audit committee expertise will effectively restrain the earnings management.